For points to lie on a line, they must satisfy the equation.

3x-y=4

Using point (2, 2) : 3(2)-2 =6-2=4.....this means (2, 2) lies on the line since it satisfies the equation.

Using point (1, -1) : 3(1)-(-1)=3--1

=3+1

=4.....this means (1, -1) lies on the line since it satisfies the equation.

Using point (-2, -5) : 3(-2)-(-5)=-6+5

=-1...this means (-2, -5) does not lie on line since it does not satisfy the equation.

Using point (1, 2) : 3(1)-2=1....this means (1, 2) does not lie on the line since it does not satisfy the equation.

Using point (0, -4 ): 3(0)-(-4) =0+4

=4...this means (0, -4) lies on the line since it satisfies the equation.

3x-y=4

Using point (2, 2) : 3(2)-2 =6-2=4.....this means (2, 2) lies on the line since it satisfies the equation.

Using point (1, -1) : 3(1)-(-1)=3--1

=3+1

=4.....this means (1, -1) lies on the line since it satisfies the equation.

Using point (-2, -5) : 3(-2)-(-5)=-6+5

=-1...this means (-2, -5) does not lie on line since it does not satisfy the equation.

Using point (1, 2) : 3(1)-2=1....this means (1, 2) does not lie on the line since it does not satisfy the equation.

Using point (0, -4 ): 3(0)-(-4) =0+4

=4...this means (0, -4) lies on the line since it satisfies the equation.